Higher Intake of PUFAs Is Associated with Lower Total and Visceral Adiposity and Higher Lean Mass in a Racially Diverse Sample of Children. Issue 9 (12th August 2015) - Cardel, Michelle; Lemas, Dominick J; Jackson, Kristina Harris; Friedman, Jacob E; Fernández, José R
Abstract: Background: Polyunsaturated fatty acids (PUFAs) are associated with protection from obesity-related phenotypes in adults; however, the relation between reported intake of PUFAs with body-composition outcomes in children remains unknown. Objective: Our objective was to examine how self-reported intakes of PUFAs, including total, n–6 (ω-6), and n–3 (ω-3) PUFAs and ratios of n–6 to n–3 PUFAs and PUFAs to saturated fatty acids (SFAs), are associated with measures of adiposity and lean mass (LM) in children. We hypothesized that higher self-reported intakes of PUFAs and the ratio of PUFAs to SFAs would be positively associated with LM and negatively associated with total adiposity. Methods: Body composition and dietary intake were measured in a racially diverse sample of 311 children (39% European American, 34% African American, and 27% Hispanic American) aged 7–12 y. Body composition and abdominal fat distribution were measured by dual-energy X-ray absorptiometry and computed tomography scans, respectively. Self-reported dietary intakes (including total PUFAs, n–3 PUFAs, n–6 PUFAs, and SFAs) were assessed by using two 24-h recalls. Independent-sample t tests and multiple linear regression analyses were conducted. Results: Total PUFA intake was positively associated with LM ( P = 0.049) and negatively associated with percentage of body fat (%BF; P = 0.033) and intra-abdominal adipose tissue (IAAT; P = 0.022). A higher ratio of PUFAs to SFAs was associated with higher LM ( P = 0.030) and lower %BF ( P = 0.028) and IAAT ( P = 0.048). Intakes of n–3 and n–6 PUFAs were positively associated with LM ( P = 0.017 and P = 0.021, respectively), and the ratio of n–6 to n–3 PUFAs was negatively associated with IAAT ( P = 0.014). All results were independent of biological, environmental, and genetic covariates. Conclusions: Our results show that a higher self-reported intake of PUFAs and a higher ratio of PUFAs to SFAs are positively associated with LM and negatively associated with visceral adiposity and %BF in a healthy cohort of racially diverse children aged 7–12 y. This trial was registered at clinicaltrials.gov as NCT00726778.